Whole Genome Sequencing: Bridging One-Health Surveillance of Foodborne Diseases - Gerner-Smidt, Peter; Besser, John; Concepción-Acevedo, Jeniffer; Folster, Jason P.; Huffman, Jasmine; Joseph, Lavin A.; Kucerova, Zuzana; Nichols, Megin C.; Schwensohn, Colin A.; Tolar, Beth (Frontiers in Public Health, 2019)
Infections caused by foodborne pathogens are not just transmitted through food. They are often transmitted through contact to animals, other humans or the environment. Many foodborne outbreaks also ultimate originate from these sources. For this reason, such outbreaks are best investigated through a One Health approach working across human, animal and environmental sectors and disciplines. Outbreak strains or clones that have propagated and continue to evolve in non-human sources and environments often show more sequence variation that observed in typical monoclonal point-source outbreaks. This represents a challenge when using whole genome sequencing (WGS), the new gold standard for molecular surveillance of foodborne pathogens, for outbreak detection and investigation. In this review, using recent examples from outbreaks investigated in the United States (US) some aspects of One Health approaches that have been used successfully to solve such outbreak are presented. These include using different combinations of flexible WGS based case definition, efficient epidemiological follow-up, traceback, surveillance and testing of potential food and environmental sources and animal hosts.